To be or not to be, a virgin: exploring selected Filipino women's perspective on virginity - Kate Anne G. Cendana. 4 0 16; 5 (2018)
ABSTRACT: Modern Filipino women view virginity as a gift and reported that it should be given after marriage because Filipino women believe that sex is a gift from God. Virgin and non-virgin women still see significance in women's virginity despite of not being a virgin anymore because it could be a basis of women's worth and self-respect. Modern virgin Filipino women persist in being a virgin because they are not yet ready and sure to the person they are being with and especially because they believe that virginity is a commandment from God while non-virgin women have given up their virginity out of curiosity and because of too much emotional affection. Women tend not to discuss anything about virginity and sex with their family because of the pre-judgements they receive from their own parents. In contrast, they laugh about virginity and sex with their friends and talk about it bluntly and think that technology and media have a great impact on modern Filipino culture. In addition to this, modern Filipino women see religion as their own guidance and that they are consider marriage and the emotional attachment they have with their partner before giving up their virginity.
UndergraduateThesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2